2018
DOI: 10.14366/usg.17028
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography-guided 14-gauge core biopsy of the breast: results of 7 years of experience

Abstract: PurposeThis study assessed the outcomes of ultrasound (US)-guided core needle biopsies (CNBs) of breast lesions with at least 2 years of follow-up to determine the false-negative rate and to evaluate the diagnostic accuracy of CNB.MethodsWe retrospectively analyzed 13,254 consecutive US-guided 14-gauge CNBs for breast lesions. We excluded biopsies if non-malignant biopsy result was not confirmed by surgical excision or US-guided vacuum-assisted biopsy, or fewer than 2 years of follow-up data were available. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 36 publications
1
12
0
2
Order By: Relevance
“…A prospective study of pathologically confirmed 110 lesions showed that DBCT provided high-quality images of the breast and could help radiologists to diagnose malignant breast lesions, as compared with ultrasound and digital mammography (He, et al 2016). In a recent study, DBCT was used to identify breast lesion and was compared with BI-RADS Mammography Atlas, the estimated overall sensitivity of the readers was 0.969, and the specificity was 0.529 (Jung, et al. 2017).…”
Section: Accuracy Of Other Modalities For Breast Cancer Diagnosismentioning
confidence: 99%
“…A prospective study of pathologically confirmed 110 lesions showed that DBCT provided high-quality images of the breast and could help radiologists to diagnose malignant breast lesions, as compared with ultrasound and digital mammography (He, et al 2016). In a recent study, DBCT was used to identify breast lesion and was compared with BI-RADS Mammography Atlas, the estimated overall sensitivity of the readers was 0.969, and the specificity was 0.529 (Jung, et al. 2017).…”
Section: Accuracy Of Other Modalities For Breast Cancer Diagnosismentioning
confidence: 99%
“…A later study in 2005 with long-term follow-up reported a false-negative rate of 3.7% for 14-gauge US-guided CNB, with three delayed diagnoses of cancer occurring at the site of prior CNB [ 5 ]. However, recent studies published in the last decade have reported slightly lower false-negative rates of US-guided CNB, ranging from 0.1% to 2.5%, with most cases identified because of discordance between imaging results and CNB histologic findings ( Table 1 ) [ 7 - 11 , 14 , 15 ]. The reported underestimation rate of high-risk lesions through US-guided CNB, a category primarily composed of atypical ductal hyperplasia (ADH) lesions in most studies, ranges from 24.5% to 65% [ 7 , 8 , 10 , 16 ].…”
Section: Review Of Us-guided Breast Biopsymentioning
confidence: 99%
“…Percutaneous imaging-guided breast biopsies are easy, reliable and cost-effective that has taken the place of excisional biopsies and thus, the form of standard diagnostic procedure (1)(2)(3)(4). Percutaneous biopsies could be performed through stereotactic or ultrasound guidance.…”
Section: Introductionmentioning
confidence: 99%